2019
DOI: 10.7150/ijbs.36995
|View full text |Cite
|
Sign up to set email alerts
|

MiR-93 regulates vascular smooth muscle cell proliferation, and neointimal formation through targeting Mfn2

Abstract: Background/Aims: Vascular smooth muscle cell (VSMC) hyperplasia plays important roles in the pathogenesis of many vascular diseases, such as atherosclerosis and restenosis. Many microRNAs (miRs) have recently been reported to regulate the proliferation and migration of VSMC. In the current study, we aimed to explore the function of miR-93 in VSMCs and its molecular mechanism.Methods: First, qRT-PCR and immunofluorescence assays were performed to determine miR-93 expression in rat VSMCs following carotid artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 39 publications
4
33
0
1
Order By: Relevance
“…4c) and that Mfn2 can perform as a target gene for miR-214-3p to regulate cell proliferation. These results are consistent with previous reports, for instance, where Feng et al [39] reported that miR-93 regulates vascular smooth muscle cell proliferation by targeting Mfn2. Additionally, miR-497 promotes cardiomyocyte proliferation by downregulating the expression of Mfn2 [40].…”
Section: Discussionsupporting
confidence: 94%
“…4c) and that Mfn2 can perform as a target gene for miR-214-3p to regulate cell proliferation. These results are consistent with previous reports, for instance, where Feng et al [39] reported that miR-93 regulates vascular smooth muscle cell proliferation by targeting Mfn2. Additionally, miR-497 promotes cardiomyocyte proliferation by downregulating the expression of Mfn2 [40].…”
Section: Discussionsupporting
confidence: 94%
“…Previously, miR-15b promoted platelet-derived growth factor signaling, thereby increasing the proliferation of vascular smooth muscle cells ( Kim and Kang, 2013 ). Consistently, recent research shows that miR-93 promotes migration and proliferation of VSMCs targeting Mfn2 ( Feng et al, 2019 ). Additionally, let-7g and miR-98 protected the blood–brain barrier in the context of neuroinflammation ( Rom et al, 2015 ).…”
Section: Discussionsupporting
confidence: 72%
“…MicroRNAs (miRNAs/miRs) control diverse cellular functions by negatively modulating the expression of genes. A large number of studies have confirmed that dysregulated miRNAs are involved in the development of neointimal hyperplasia (9)(10)(11)(12). Evidence has demonstrated that the expression of miR-24 differs significantly between patients with atherosclerosis and age-matched controls, whereas overexpression of miR-24 can suppress the development of atherosclerosis (13).…”
Section: Introductionmentioning
confidence: 98%